Pengaruh Pajak, Size, Debt Covenant, Dan Kepemilikan Asing Terhadap Transfer Pricing Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2020 - Raden Januari Pangaribuan (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2021)
practices carried out by companies where the company wants maximum profit, by suppressing expenses that can directly reduce the profits earned by the company by means of transfer pricing. The purpose of this study was to determine and analyze the effect of tax, size, debt covenant, foreign ownership in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The population in this study were 154 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The sample of this study used a purposive sampling technique, so that 11 sample companies were obtained for 4 years of observation (2017-2020) with a total of 44 sample companies. The data analysis technique used is logistic regression analysis using the SPSS 25 statistical test tool. The results of the study found empirical evidence that tax and foreign ownership variables have a significant effect on transfer pricing. Meanwhile, size, debt covenants have no significant effect on transfer pricing